IKBKE, a prognostic factor preferentially expressed in mesenchymal glioblastoma, modulates tumoral immunosuppression through the STAT3/PD‐L1 pathway. Issue 3 (23rd July 2020) - Yi, Li; Guo, Gaochao; Li, Jiabo; Fan, Xiaoguang; Li, Tao; Tong, Luqing; Liu, Peidong; Wang, Xuya; Yuan, Feng; Yu, Shengping; Huang, Qiang; Yang, Xuejun
Abstract: Inhibitor of nuclear factor kappa‐B kinase subunit epsilon (IKBKE) plays critical roles in the proliferation, invasion, and epithelial‐mesenchymal transition (EMT) of glioblastoma (GBM). However, as an immune response factor, few studies have focused on the role of IKBKE in the glioblastoma‐mediated immunosuppressive microenvironment. Here, we found a higher IKBKE expression level in gliomas corresponding to higher malignancy of the tumor. The highest level of IKBKE expression was examined in the core region of GBM tissues as well as the mesenchymal subtype, which are featured with necrosis, immunocyte infiltration, and immunosuppression. Further in silico analysis demonstrated that the JAK/STAT as the signaling pathway most associated with IKBKE in mesenchymal GBM. The co‐expression patterns of IKBKE, pSTAT3, and PD‐L1 were detected within GBM tissues. Mechanistically, IKBKE could interact with STAT3 and thus enhancing the phosphorylation level of STAT3 and its nuclear translocation. In addition, pSTAT3 could transcriptionally regulate the expression of PD‐L1 through binding to its promoter. In vivo results further confirmed the inhibitory effect of the IKBKE downregulation on tumor growth. Collectively, our findings suggest IKBKE as the central node in the crosstalk between NF‐κB and STAT3 signaling within mesenchymal GBM. Targeting GBM through inhibiting IKBKE could restrain tumor growth and tumor‐mediated immunosuppressive environment. Abstract : 1. Higher IKBKE expression was detected in higher grades of glioma. 2. IKBKE is enriched in mesenchymal GBM, which confers immunosuppressive signature. 3. IKBKE correlates with JAK/STAT signaling in MES GBM. 4. IKBKE activates the phosphorylation of STAT3, which transcriptionally regulates PD‐L1 expression.